2005
DOI: 10.1038/modpathol.3800356
|View full text |Cite
|
Sign up to set email alerts
|

Successful retrieval of fine-needle aspiration biopsy material from previously stained smears for immunocytochemistry: a novel technique applied to three soft tissue tumors

Abstract: Fine-needle aspiration biopsies of soft tissue tumors are often not fully diagnostic on conventional Papanicolaou or Giemsa stains. Often, more useful information can be gleaned from preparing cell blocks, which are amenable to immunocytochemistry. However, sufficiently diagnostic cell block material is not always forthcoming. We subvent this problem by employing a new 'cytoscrape' technique to create cell blocks from previously Papanicolaou-stained smear material in two cases of mesenchymal tumors where smear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…They found cytoscrape cell blocks were able to provide not only equally good cytomorphology as conventional cell blocks, but also opportunities to test a diagnostic panel for ICC. 31 A similar experience with this method has also been reported by Nga et al 35 Cytoscrape cell block opens up a unique way to make use of nondiagnostic thick cell clusters and blood clot -covered cell aggregates on smear slides. However, the studies regarding this methodology were all small with only three to seven cases for ICC analysis.…”
Section: Cell Block Techniquementioning
confidence: 69%
“…They found cytoscrape cell blocks were able to provide not only equally good cytomorphology as conventional cell blocks, but also opportunities to test a diagnostic panel for ICC. 31 A similar experience with this method has also been reported by Nga et al 35 Cytoscrape cell block opens up a unique way to make use of nondiagnostic thick cell clusters and blood clot -covered cell aggregates on smear slides. However, the studies regarding this methodology were all small with only three to seven cases for ICC analysis.…”
Section: Cell Block Techniquementioning
confidence: 69%
“…Cell blocks were made for patients 1 and 2 by scraping material from highly cellular smears into a gel, and then processing it by routine histology, somewhat akin to what has been previously described. 16 The cytologic features are summarized in Table I (Figs. 1-4).…”
Section: Cytologic Findingsmentioning
confidence: 99%
“…Nga et al described a similar method for making clots from 3 mesenchymal tumors. 11 Those authors reported that the cohesive mesenchymal nature of the tumor cells enables the cells to be scraped off the slide, because they form cohesive clusters that withstand the mechanical stresses of being removed from the smear and embedded in paraffin blocks. We demonstrated that this method also may be applied successfully to noncohesive epithelial tumors without microbiopsies on the slides.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiopsies from stained smears were picked up and processed directly through paraffin. 11,12 However, microbiopsies often are not present on the smears.…”
mentioning
confidence: 99%